Docência nos anos finais do ensino fundamental e suas relações com as tecnologias digitais - Oliveira, Raquel Mignoni de (My University, 2020)
This dissertation legitimizes itself to the field of investigation about the teacher formation passing through the teaching and the innovations in the educational scope. This research aims to investigate teacher education and its contributions to the use of digital technologies in educational practices in a private school in Serra Gaúcha. The problematizations of this study focus, through the theoretical dialogue with Paulo Freire and António da Nóvoa, the observation of how teacher education contributes to the use of digital technologies in educational practices in the Final Years of a private school. This research understands that training is the process that supports teaching practice and is constituted from various movements, such as graduation, courses, symposiums, as well as looking at their practice or the exchange of experience between peers at school. These activities that constitute the teaching subject, because of the insertion of technologies in the school context, cause a dislocation concerning the role of teacher and student, placing them and integrating them as active individuals in the teaching and learning processes. From this perspective, it is discussed how this corpus reverberates in educational practices at school, highlighting the emerging teaching movement of the current educational context. The investigative paths followed the methodological paths of a qualitative research of analytical-interpretative nature. This investigation has as evidence sources institutional documents and semi-structured interviews conducted with teachers who work at elementary school from a private school in Serra Gaucha. To explore the investigated data that emerged from the interviews used the Bardin Content Analysis (2016). The main theoretical contributions selected to theoretically support the investigative pathways, inspire descriptions, substantiate interpretations and reflections are based on Paulo Freire, António da Nóvoa, Pierre Lévy, Denise Leite, and Débora Valletta and Lucia Giraffa, among other theoretical immersions. Three categories emerged from the teaching lines: “Teacher Training”; “Educational Practice” and “Digital Technologies Contributions ”, from which we obtained two subcategories each: as regards to the first category we have: “Digital Technologies Contributions” and Digital Technologies”; the second presented: “Methodological and evaluative processes” and “Educational resources”; and the third: “Potentials and motivation generated by the digital technologies use” and “Digital technologies as Innovation and as Support”. The study showed that teacher education meddles with educational practices and can contribute to the digital technologies use at school, however, preparing teachers for the use of digital technologies in educational practices does not only mean teaching to use of tools and/or software, the biggest challenge in concurrent times is to unleash a more active attitude in the teacher, being the knowledge mediator, beginning the student to the learning center, also making him/her more active in the teaching and learning processes.
Esta dissertação se legitima ao campo de investigação sobre a formação docente perpassando pela docência e pelas inovações no âmbito educacional. Esta pesquisa se propõe investigar a formação docente e suas contribuições para o uso das tecnologias digitais nas práticas educativas em uma escola de ensino privado na Serra Gaúcha. As problematizações deste estudo têm como foco, por meio da interlocução teórica com Paulo Freire e António da Nóvoa, dentre outros autores, investigar a formação docente e a sua possível contribuição para o uso das tecnologias digitais nas práticas educativas nos Anos Finais de uma escola privada. Na tessitura desta investigação, entende-se que a formação é o processo que sustenta a prática docente e é constituída a partir de vários movimentos, como graduação, pós-graduação, cursos, simpósios, bem como a reflexão e o olhar para sua própria prática ou na troca de experiência entre pares na escola. Esses movimentos de formação que constituem o sujeito docente, diante da inserção das tecnologias no contexto escolar, provoca um deslocamento em relação ao papel do professor e do aluno, situando-os e integrando-os como indivíduos ativos nos processos de ensinar e aprender. Nessa perspectiva, coloca-se em discussão como esse corpus reverbera nas práticas educativas na escola, evidenciando a movimentação docente emergente do contexto atual da educação. Os percursos investigativos seguiram trilhos metodológicos de uma pesquisa qualitativa de cunho analítico-interpretativa, tendo como fontes de evidência documentos institucionais e entrevistas semiestruturadas realizadas com os docentes que atuam no Ensino Fundamental Anos Finais de uma escola privada da Serra gaúcha. Para exploração dos dados investigados que emergiram das entrevistas, foi utilizada a Análise de conteúdo de Bardin (2016). Os principais aportes teóricos selecionados para sustentar teoricamente os percursos investigativos, inspirar as descrições, fundamentar as interpretações e reflexões estão fundamentados em Paulo Freire, António da Nóvoa, Pierre Lévy, Denise Leite e Débora Valletta e Lúcia Giraffa, entre outras imersões teóricas. Três categorias emergiram das falas docentes: “Formação docente”; “Prática educativa” e “Contribuições das tecnologias digitais”, a partir delas obteve-se duas subcategorias cada: no que se refere a primeira categoria tem-se: “Contribuições das tecnologias digitais” e Tecnologias digitais”; a segunda apresentou:“Processos metodológicos e avaliativos” e “Recursos educativos”; e a terceira: “Potencialidades e motivação gerada pelo uso das tecnologias digitais” e “Tecnologias digitais como Inovação e como Suporte”. O estudo mostrou que a formação docente interfere nas práticas educativas e podem contribuir para o uso das tecnologias digitais na escola, contudo, preparar os professores para o uso das tecnologias digitais nas práticas educativas, não significa apenas ensinar o uso de ferramentas e/ou software, o grande desafio na contemporaneidade é desencadear no docente uma postura mais ativa, sendo o mediador do conhecimento, trazendo o aluno para o centro da aprendizagem, tornando-o, também, mais atuante nos processos de ensino e de aprendizagem.
Keywords: Professores - Formação; Inovações educacionais; Ensino fundamental - Serra, Região (RS); Teachers, Training of; Educational innovations; Elementary School - Serra, Região (Brazil)